Proximity-dependent biotin labeling in testicular germ cells identified TESMIN-associated proteins - Seiya Oura; Akinori Ninomiya; Fuminori Sugihara; Martin M. Matzuk; Masahito Ikawa (Scientific Reports, 2022)
Abstract Characterization of protein–protein interactions (PPI) is a key to understanding the functions of proteins of interest. Recently developed proximity-dependent biotin identification (BioID) has been actively investigated as an alternative PPI mapping method because of its usefulness in uncovering transient PPI. Here, as an example of proximity labeling proteomics application in the testis, we generated two transgenic mouse lines expressing two biotin ligases (BioID2 or TurboID) fused with TESMIN, which translocates from the cytosol to the nucleus during meiotic progression and is required for reproduction. The BioID2 transgene, albeit not the TurboID transgene, rescued fertility defects of the Tesmin KO male mice, indicating that the TESMIN-BioID2 fusion can physiologically replace TESMIN. Furthermore, biotinylated protein pull-down and affinity-purification followed by mass spectrometry using the TESMIN-BioID2 transgenic mice captured components of the MYBL1–MuvB complex that regulate cell-cycle gene expression. Thus, our study shows that proximity labeling proteomics can be applied in male germ cells, although the choice of biotin ligase needs to be carefully tested.